Kurikulum pendidikan dari perspektif Islam dalam konteks pendidikan di Malaysia - Hashim, Rosnani (Yayasan Takmir, 2001)
This paper assumes that the problems confronting the Muslim ummah throughout the world stem from education which itself is plagued with a lot of challenges. It attempts to analyze the educational curriculum, which is a major aspect of education that lends its shape. The paper argues that many Islamic educational institutions today suffer from weak curricula. To highlight this, the writer prefaces her paper with a discussion on the theory of curriculum development which comprises four basic components: educational objectives; learning experiences, organization of the learning experiences and evaluation of achievement of objectives. The most conspicuous weakness is the ambiguity or sometimes the non-existence of a clear philosophy of education which acts as the basis for any educational institution. As a result the curriculum formulated does not reflect the philosophy which is supposed to underlie it. Instead, it reflects that of an alien philosophy such as the liberal, secular philosophy. The analysis also shows that the learning experiences provided are in some instances inadequate and not in line with the educational objectives. Based on these weaknesses and the divergence of curriculum from the philosophy, the paper presents a few steps for them to converge and the weaknesses to be redressed.